Reaching Students in Online Courses Using Alternative Formats - Fidalgo, Patricia; Thormann, Joan (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This research was conducted to explore whether students enrolled in graduate level courses found some Universal Design for Learning (UDL) strategies useful and if they actually used them. The strategies we investigated were presenting course information in alternative formats including PowerPoints with voiceover, screencasts, and videos as an alternative to text resources. In addition, students were invited to submit assignments in alternative formats as well as text. To examine these strategies, we used a student questionnaire, analytics from Blackboard, and assignment formats students used. The results indicate that text was the preferred format for accessing course information and resources as well as assignment submission. However, a substantial number of students acknowledged the benefits of using alternative formats and a smaller percentage used them. We suggest that instructors take advantage of UDL strategies that were examined since a sufficient number of students used them and because learning styles differ. We can reach more students by using these strategies.